Effect of administration of flunixin meglumine on pregnancy and pregnancy loss rates after transfer of low-quality embryos in dromedary camels - Karen, Aly; Ihsan, Muhammad Manzoor; Ihsan, Muhammad Babar; Rahman, Raza Ur; Muthukumaran, Shanmugavelu; Abd-Elfattah, Ahmed (Small ruminant research, 2025)
The present study aimed to evaluate effects of administering flunixin meglumine (FM) to recipient females at the transfer of a small-sized embryo and on the third and fourth days after ET on pregnancy and pregnancy loss rates. A total of 227 small-sized embryos (< 450 µm in diameter) were recovered at Day 9 after mating of the donors and transferred individually into synchronized recipients (Day 6.5 after ovulation). Recipients were randomly allocated into three groups: Group 1 (n = 72) received FM (1.1 mg/ Kg) intravenously at the time of ET; Group 2 (n = 72) received FM at the time of ET and on the third and fourth day after ET (days of maternal recognition of pregnancy; MRP) and Group 3 (n = 83) received no treatment. Pregnancy diagnosis was conducted on Day 10 after ET by progesterone test and by transrectal ultrasonography on Days 30 and 60 of gestation. Pregnancy rates on Days 19, 30, and 60 were non-significantly lower in Group 1 (50.0, 47.2, and 45.8 %, respectively) compared to those in Group 2 (61.1, 54.2, and 47.2 %) and Group 3 (60.2, 55.4, and 50.6 %). Pregnancy loss rate was non-significantly higher in Group 2 (22.7 %) compared to those of Group 1 (8.3 %) and Group 3 (16.0 %). In conclusion, administration of FM at ET may not improve pregnancy rate after the transfer of the small-sized embryos, whereas administration of FM at days of MRP may increase pregnancy losses. •Transfer of small-sized embryos resulted in a lower pregnancy rate than large ones.•Injection of flunixin meglumine into recipients at ET and on the 3rd and 4th day after ET did not affect the pregnancy rate.•Injection of FM on the 3rd and 4th days after ET may increase pregnancy losses.